2014
DOI: 10.1177/0969733013515488
|View full text |Cite
|
Sign up to set email alerts
|

Swedish nurses’ perceptions of influencers on patient advocacy

Abstract: The nurse's character traits are the fundamental influencer to patient advocacy, but in order to be comfortable and secure when advocating for patients, nurses also need to be familiar with both the patient and the situation. A supposition could be that all influencers interact, which needs to be further addressed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 30 publications
2
51
0
6
Order By: Relevance
“…In the construct facilitators to the practice of advocacy, personal values and professional skills were highlighted as the main sources of support for health advocacy actions. Thus, the characteristics of nurses can directly and positively influence the exercise of patient advocacy, such as when nurses have a higher sense of confidence that comes from their professional self-worth (7,16,(23)(24) . Similarly, the knowledge and skills of nurses are considered determining factors in the practice of health advocacy and can be developed in the formation and/or during work experience through continuing education programs (20,(24)(25) , providing opportunities for them to be adequately trained to deal with situations that require defending patients' rights.…”
Section: Resultsmentioning
confidence: 99%
“…In the construct facilitators to the practice of advocacy, personal values and professional skills were highlighted as the main sources of support for health advocacy actions. Thus, the characteristics of nurses can directly and positively influence the exercise of patient advocacy, such as when nurses have a higher sense of confidence that comes from their professional self-worth (7,16,(23)(24) . Similarly, the knowledge and skills of nurses are considered determining factors in the practice of health advocacy and can be developed in the formation and/or during work experience through continuing education programs (20,(24)(25) , providing opportunities for them to be adequately trained to deal with situations that require defending patients' rights.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, providing guidance was the action most frequently performed by nurses to ensure the rights of children, which is in agreement with studies addressing advocacy on the part of nurses in different health settings, showing that advocacy especially includes providing guidance and clarification to patients in order to promote their autonomy. 8,13 In regard to the first category Nurses' actions to ensure the right to life and dignity, the main actions performed by nurses are based on providing guidance and promoting autonomy, demanding improved infrastructure conditions within the unit and also patient safety. It is worth noting that the establishment of the Universal Declaration of the Rights of the Child in 1959 significantly and profoundly impacted the attitudes of nations toward childhood, reaffirming the importance of ensuring universality, objectivity and equality when considering issues related to the rights of children.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence indicating the need to pursue it as a career goal in nursing, there still is not a defined concept for patient advocacy. In 1973, international nursing practice codes included patient advocacy as an ethical and legal role for nurses and since then several studies have pointed to actions and features that are intended to assist and expand the exercise of patient advocacy in nursing practice (7)(8)(9)(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several investigations have shown that the actions of nurses as patient advocates are intended to help them in obtaining appropriate health care; defending their rights, ensuring the quality of care; and serving as a link between the patient and the health care environment (7)(8)(9)(10)(11)(12)(13)(14) . However, it is emphasized that in order to define and describe the actions of nurses in patient advocacy, it is necessary to consider that such actions are not static and fixed, but influenced by particular characteristics of individuals, organizations, relationships, medical conditions and environments (15) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation